Novel implementation of natural fibro-granular materials as acoustic absorbers. (October 2018) - Mamtaz, Hasina; Hosseini Fouladi, Mohammad; Narayana Namasivayam, Satesh; Sayed, Saadman H; Sayed, Tahani H; Ghassem, Masomeh; Baniotopoulos, Charalampos
In this study, a new innovative fibro-granular composite was prepared as a natural acoustic material by combining fibrous and granular materials. Delany–Bazley model and Biot–Allard techniques were utilized to estimate the absorption coefficient of the developed composite material. The predicted values were validated through an analytical outcome employing Johnson–Champoux–Allard technique and an experimentally measured value which were conducted in an impedance tube. The outcomes showed the reflection of the good agreement between the analytical and experimental methods. The current research concluded that the introduction of granular materials provides significant contribution in enhancing the surface area within the composite, thereby achieving a promising acoustic absorption in the low-frequency region which is below 1 kHz. In addition, the current research also reports that, like Johnson–Champoux–Allard model, Delany–Bazley and Biot–Allard models are also two efficient analytical tools for predicting the significant low-frequency acoustic absorption performance of a fibro-granular composite.